Association Between Donor/Recipient BK Viral Serostatus and Risk of BK Viraemia Post-Transplantation. (July 2018) - Chong, Stephanie; Atkinson, Claire; Banga, Neal; Harber, Mark; Reeves, Matthew; Magee, Ciara N
Abstract : Introduction: The development of BK viraemia, and subsequently, BK nephropathy is a potentially devastating event associated with kidney transplant loss. In contrast to other clinically important viruses (e.g., CMV), donor and recipient BK serostatus is not routinely established pre-transplantation. It is therefore unclear whether active infection post-transplantation is donor-derived, due either to primary infection in a previously BK-naïve recipient or re-infection with a viral genotype not previously encountered, or recipient-derived, due to re-activation of latent virus as a consequence of immunosuppression. We investigated the BK serostatus of UK organ donors and examined the association of donor/recipient serostatus mismatch with development of BK viraemia post-transplantation. Methods: Serum samples from 95 kidney donors, matched to 101 organs transplanted in our unit, were obtained from the national Quality in Organ Donation (QuOD) biobank; 10 recipients of these organs had developed BK viraemia (threshold >100 viral copies/ml). Donor serum was tested for BK IgG via ELISA, and for the presence of viral DNA. Recipient clinical data, including development of BK viraemia, time to/duration of viraemia, and peak viral load, were collected. Pre-transplant serum samples from 26 matched recipients, 5 with documented BK viraemia, were similarly analyzed and linked to donor serostatus. Results: Of 95 donors evaluated, only 46 (48.4%) were seropositive for BK, none with detectable viraemia. 10/47 (21.3%) patients who received kidneys from BK seropositive donors developed BK viraemia, versus 6/54 (11.1%) patients who received kidneys from seronegative donors. The mean peak viral load was 100-fold higher in recipients of a kidney from a seropositive versus a seronegative donor (428331 vs 3293 copies/ml). Similar rates of BK seropositivity (14/26;53.8%) were seen in recipients pre-transplant. 4 (33.3%) seronegative recipients developed viraemia compared to 1 (7.1%) of seropositive recipients; 4/5 (80%) were seronegative pre-transplant, all 5 received a kidney from a seropositive donor. Conclusion: In our pilot study, BK viraemia rates were increased in seronegative recipients, and in patients who received kidneys from seropositive donors. Our data suggest that determining the donor/recipient serotype mismatch may be a useful tool for stratifying the risk of BK disease.